Violence Against The Wife – Protection Available Under The Domestic Violence Act 1994 - Mohd Yusoff, Jal Zabdi (Journal of Malaysian and Comparative Law, 2001)
Vioence perpetrated behind closed doors subsists despite the rapid progress in human civilisation. Domestic violence is synonymous with the household, as its victims are usually family members, such as wives, children, incapacitated adults and sometimes even husbands. Every family member in any household is a potential victim of violent acts committed by another member of the family and this phenomenon is not limited to any specific category of people distinguished by ethcnic, origin, race or religion.